Konsep Perencanaan dalam Perspektif Al Qur’an - lala, Rizki Lala Amelia; Hamidullah Mahmud (UIN Sulthan Thaha Saifuddin Jambi, 2024)
This article aims to find out the function of planning in the view of the Qur'an and can be used as a strengthening foundation that Islam also views the importance of planning. Considering that planning is a basic process for everything, such as choosing targets and determining how to achieve them. Therefore, a company or an educational institution must set goals and targets to be achieved before carrying out the planning processes. This article is a type of qualitative research with a library research approach. The results of the analysis show that planning is a first process when you want to do work, both in the form of thinking and a framework so that the goals to be achieved get optimal results. Likewise, in Islamic education, planning must be the first step that is really considered by managers and administrators of Islamic education. Because planning is an important part of success, mistakes in determining Islamic education planning will have very fatal consequences for the sustainability of Islamic education, as explained in the Qur'an and hadith about the importance of the function of planning.